Norwegian elite handball and football referees` self-reported intention to quit officiating: The role of the dualistic model of passion - Johansen, B. T.; Erikstad, M. K.; Haugen, T. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
Introduction Researchers have raised concerns about sport referee attrition and its potential negative impact on the games quality [1]. Previous studies have highlighted that passionmay prevent dropout from sport activities [2,3], still empirical evidence from the context of sport refereeing is requiring. Hence, the aim of the present study was to investigate the predictive value of passion on intentions to quit among Norwegian elite sport referees. Methods The participants were 224 Norwegian elite referees of handball (n = 111, m age = 35.3 years, 13.5% females) and football (113, m age = 30.8 years, 8% females) who had been referees for an average of 14.4 years (sd = 7.77 years; min: 4, max: 37) and a referee at the present level for 6.8 years (sd = 6.20 years, min: 1, max: 32). In a section of the web-based survey was a question constructed based on the work of Van Yperen [4] assessing participants` intentions to quit as an elite referee (e.g., `Do you sometimes think about quitting as elite referee?`). The referees could choose between three alternative answers: 1. I never think about quitting, 2. I sometimes think about quitting, and 3. I often think about quitting. The 12-item Passion Scale [2,3] was used to assess the referees` type of passion that characterized their officiating. Results The number of complete cases for the present study was N = 184. Overall, 50.5 % (n = 93) of the referees had an intention to quit refereeing. A logistic regression was performed to assess the predictive value of harmonious passion and obsessive passion on the likelihood of intention to quit officiating. The logistic regression model was statistically significant, *2(1,181) = 33.319, p < .001. The model explained 22% (Nagelkerke R2) of the variance in intention to quit. The odds ratio for harmonious passion was 0.397, meaning that one unit increase on the harmonious passion scale (1-7) was associated with a decrease of 60 % in the odds of having an intention to quit officiating. Additionally, no statistically significant effect was found for obsessive passion on intention to quit officiating. Conclusion The present findings revealed that harmonious passion significantly decreased the likelihood of intending to quit officiating, emphasizing the importance of nurturing a positive and balanced passion in sports refereeing. The study offers insights that could help address concerns raised by researchers regarding elite sport referee attrition and its potential impact on game quality.